Expanding Candidacy for Nipple-sparing Mastectomy in Women with Large or Ptotic Breasts: Staged Reconstruction Outcomes. Issue 1 (25th January 2023) - Barnes, Laura L.; Foster, Rob; Mukhtar, Rita A.; Esserman, Laura J.; Ewing, Cheryl; Alvarado, Michael; Wong, Jasmine; Piper, Merisa
Abstract : Background: Development of the nipple-sparing mastectomy (NSM) technique has dramatically improved breast reconstruction, and preservation of the nipple–areolar complex (NAC) positively influences patient satisfaction. However, women with large, ptotic breasts have historically not been candidates for NAC preservation due to impaired perfusion of the NAC leading to NAC loss. Although reduction mammoplasty has been reported as a strategy to increase candidacy for NSM, success rates and surgical outcomes for this staged approach are not well described in heterogeneous clinical scenarios. Methods: We performed a retrospective chart review of all patients who underwent reduction mammoplasty followed by NSM at our institution between January 2014 and September 2020. Clinical and surgical characteristics were collected. All surgical complications, including NAC loss rates, were analyzed. Results: Forty-one patients (74 breasts) underwent staged NSM during the defined time period. The average time between breast reduction mammoplasty and NSM was 213 days. Overall, 94.6% of NSM resulted in successful nipple preservation. There was no significant difference in the time interval from breast reduction mammoplasty to NSM between patients who had NAC loss (208 days) and those who did not (213 days, P = 0.87). Increasing age was significantly associated with risk of NAC loss ( P = 0.002) in our cohort. Conclusions: In women with breast ptosis (which precludes safe NSM), it is possible to first offer reduction mammoplasty to preserve the NAC for future NSM. Our data suggest that 3 months between staged procedures is a safe time frame.